Patient characteristics associated with primary care PA and APRN roles. Issue 12 (December 2016) - Everett, Christine M.; Morgan, Perri; Jackson, George L.
ABSTRACT: Objectives: Physician assistants (PAs) and advanced practice registered nurses (APRNs) can perform multiple roles on primary care teams, but limited research describes the patients they serve. We sought to identify patient characteristics associated with roles of primary care PAs and APRNs. Methods: We analyzed adult respondents to the 2010 Health Tracking Household Survey with a primary care usual provider (physician, PA, or APRN). The dependent variable is the PA or APRN role. Explanatory variables include sociodemographic characteristics, attitudes toward use, delayed care, and perceived health. Results: Compared with respondents seen by physicians only, respondents seen by a PA or APRN in any role were more likely to be younger, female, living in rural areas, and put off needed medical care. Respondents seen by a PA or APRN as their usual provider were more likely to report better health. Patients seen by a PA or APRN in a supplemental role reported being sicker, more educated, and attitudinally less likely to use healthcare. Conclusions: PAs and APRNs perform different roles for different types of patients.